Field efficacy of Trichoderma viride, Bacillus subtilis and Bacillus cereus in consortium for control of Rhizoctonia solani causing black scurf disease of potato - R.K. ARORA, A.K. SOMANI* (Indian Phytopathology, 2010)
Black scurf disease (Rhizoctonia solani) of potato could significantly be reduced by treating the seed tubers with Trichoderma viride, Bacillus cereus strain B4 and B. subtilis strain B5 alone or in different combinations. Disease incidence was reduced from 72 per cent in untreated control to 42 per cent (i.e. 42 per cent reduction) and severity index from 1.6 units to 0.6 units (i.e. 62.5 per cent reduction) in seed tubers treated combinedly with the above three bio-agents.